2017
DOI: 10.1021/acs.nanolett.6b03855
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Spin-Polarized Electronic Band Structure in Monolayer Transition Metal Dichalcogenides by Optical Spectroscopy

Abstract: We study the electronic band structure in the K/K' valleys of the Brillouin zone of monolayer WSe 2 and MoSe 2 by optical reflection and photoluminescence spectroscopy on dual-gated field-effect devices. Our experiment reveals the distinct spin polarization in the conduction bands of these compounds by a systematic study of the doping dependence of the A and B excitonic resonances. Electrons in the highest-energy valence band and the lowest-energy conduction band have antiparallel spins in monolayer WSe 2 , an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
145
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(178 citation statements)
references
References 56 publications
(209 reference statements)
26
145
1
1
Order By: Relevance
“…This result makes sense, but when we increase the temperature we never obtain values as small as those reported in the experiments for MoS 2 . It is now known [55] that excitonic spectrum of TDMC's samples in SiO 2 are strongly influence by the disorder of the substrate. In this reference it is shown that encapsulated samples in h-BN have much narrower excitonic peaks.…”
Section: Resultsmentioning
confidence: 99%
“…This result makes sense, but when we increase the temperature we never obtain values as small as those reported in the experiments for MoS 2 . It is now known [55] that excitonic spectrum of TDMC's samples in SiO 2 are strongly influence by the disorder of the substrate. In this reference it is shown that encapsulated samples in h-BN have much narrower excitonic peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Here, charge tunable samples [66] or experiments in transverse magnetic fields [67,68] are expected to give a better indication on the dark-bright order in future experiments on these narrow linewidth samples. The temperature dependence of the PL peak position follows a standard hyperbolic cotangent relation [69]:…”
Section: B Temperature-induced Line Broadeningmentioning
confidence: 99%
“…Theoretical calculations show that the same double peak structure is expected also for the B band. [28][29][30] Experimentally the B À trion has been recently observed by reflectance contrast measurements in WSe 2 and MoSe 2 , [31] but attempts to detect the existence of B À (or B þ ) trion by PL have not been successful.…”
Section: Introductionmentioning
confidence: 99%